Mobilizing money : how the world's richest nations financed industrial growth - Fohlin, Caroline, 1966- (Cambridge ; New York : Cambridge University Press, 2012)
This book examines the origins of modern corporate finance systems during the rapid industrialization period leading up to World War I.
Includes bibliographical references (p. 231-255) and index.
oif 16/06/15
Loan
Keywords: Banks and banking -- History; Financial institutions -- History; Investments -- History